Variation of Cicer Germplasm to Manganese Toxicity Tolerance - Pradeep, Karthika; Bell, Richard W.; Vance, Wendy (Frontiers in Plant Science, 2020)
After aluminum, manganese toxicity is the most limiting factor for crops grown in acidic soils worldwide. But overall, research on Mn toxicity is still limited. The poor acid tolerance of chickpea may be related to Mn toxicity, but there has been no previous screening of chickpea germplasm (nor in its wild Cicer relatives, Cicer reticulatum and Cicer echinospermum) for tolerance to Mn toxicity. A screening technique was developed for tolerance to Mn toxicity using three released cultivars of chickpea (Cicer arietinum L), Ambar, PBA HatTrick, and PBA Striker; one accession each of C. reticulatum and C. echinospermum; and lupin (Lupinus angustifolius) as a Mn-tolerant check, with eight Mn concentrations of 2, 25, 50, 100, 150, 200, 250, and 500 μM Mn as MnSO4 in a low-ionic-strength nutrient solution. The plants were harvested at 14 and 28 days after Mn treatments. The nutrient uptake in shoots (young, old leaves, and the rest of the shoot) and roots was investigated. The best discrimination between tolerant and intolerant Cicer genotypes based on relative shoot dry weight, root dry weight, total root length, and scoring of toxicity symptoms was achieved at 150 μM Mn after 14 days of growth in Mn solution. Among the chickpea cultivars, the greater relative plant growth (both shoot and root) of Ambar and PBA Striker at 100–200 μM Mn contrasted with that of PBA HatTrick, while the C. echinospermum accession was more tolerant to Mn toxicity than C. reticulatum. Manganese tolerance in both domestic cultivars and wild accessions was associated with internal tolerance to excess Mn following greater uptake of Mn and translocation of Mn from roots to shoots.